Preparation of multiwall carbon nanotubes/cellulose nanocomposites stabilized by 1-butyl-3-methyl-imidazolium (bmim) - surfactants - Rabiaa Abu Azoum Ali (Universiti Pendidikan Sultan Idris, 2018)
Preparation of multiwall carbon nanotubes/cellulose nanocomposites stabilized by 1-butyl-3-methyl-imidazolium (bmim) - surfactants by Rabiaa Abu Azoum Ali